Considerações acerca das deduções de natureza constitucional do imposto sobre a renda - Castellani, Fernando Ferreira (2015)
This study aims to discuss the correct interpretation of the constitutional prescriptive statements on income tax, specifically on the deductions related to dignity and fundamental rights. The intention is to demonstrate that the concepts of income, ability to pay and the minimum conditions for subsistence and dignity should be broadly discussed and interrelated on the pursuit of fair taxation. All expenses related to personal and family costs incurred to maintain regular, everyday life should be excluded from the concept of taxable income as well as from the ability to pay concept, because, otherwise, the most basic principles applied to income tax will be violated